2020
DOI: 10.1111/imj.14904
|View full text |Cite
|
Sign up to set email alerts
|

Left anterior descending artery dissection: a rare sequela of blunt chest trauma

Abstract: Traumatic coronary artery (CA) dissection is an extremely rare sequela of blunt chest trauma. Diagnosis of CA dissection in the setting of chest trauma is challenging. While conventionally coronary angiography has been the diagnostic tool of choice, modern imaging techniques such as optical coherence tomography can further improve diagnostic accuracy and help optimise treatment strategy. The ideal treatment modality for managing CA dissection has not been established with case reports revealing a range of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Serial ECG follow-up and regional wall abnormalities on the echocardiogram can be helpful in most cases. Previous studies have reported blunt chest trauma as the cause of coronary artery dissection ( 9 , 10 ). Coronary artery dissection can sometimes lead to ST-segment elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Serial ECG follow-up and regional wall abnormalities on the echocardiogram can be helpful in most cases. Previous studies have reported blunt chest trauma as the cause of coronary artery dissection ( 9 , 10 ). Coronary artery dissection can sometimes lead to ST-segment elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of CA dissection in the setting of chest trauma is challenging. While conventionally coronary angiography has been the diagnostic tool of choice [ 4 , 5 ], modern imaging techniques such as computed tomography coronary angiography (CTCA) can further improve diagnostic accuracy and help optimize the treatment strategy [ 6 ]. This fast and non-invasive diagnostic method provides good quantitative and qualitative assessment of the coronary arteries and the aortic root.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal treatment modality for managing CA dissection has not been established yet, with case reports revealing a variety of treatment strategies [ 6 ]. Possible options include invasive techniques (percutaneous transluminal coronary angioplasty), surgical revascularization, thrombolysis (at the risk of deterioration of the dissection) and conservative treatment.…”
Section: Introductionmentioning
confidence: 99%